Development of Instructional Media DCS using LabVIEW and Arduino Platform for Instructional of Processing Control System - Ramadhan, Agus Rahmat; Adullah, Ade G.; Juanda, Enjang A. (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2016)
One of many duties of teachers is as a facilitators of students learning activities, as facilitator a teacher has to be capable in serving various kinds of instructional media. This researchÂ aims to develop instructional media by applyingÂ the computer assisted as simulation trainer of DCS in order to run processing control system, and analyzing characteristics on processing control systems, interactively, intuitive, effectively, and efficiently. This DCS/SCADA trainer is developed using LabVIEW application as the Human Machine Interface (HMI) which usually present on Distributed Control System (DCS). Arduino microcontroller as replacement for Programmable Logic Control (PLC) device. Applied controlling systems are Proportional Integral and Derivative (PID) control on single loop level and cascade loop level. From the research result by using mixed methods acquired qualitative and quantitative dataâ€™s. Data then analyzed through triangulation process by using the support of NVivo application until its validity and credibility can be approved as assessment on the instructional media which had been developed. To know the effectiveness thus testing of the student comprehension regarding of the media that is being used before has to be done by providing pretest and posttest. The results of the analysis of qualitative data obtained the information that stakeholders in the development of instructional media have confirmed agreement on the suitability of media that is developed with the curriculum in instrumentation processing control program. And the results of testing the effectiveness of this medium can be proven by the average value of the results of more than pretest posttest, the effectiveness is then expressed in Cohen-d where the results indicate a positive difference.